Inferior Outcome of Addition of the Aminopeptidase Inhibitor Tosedostat to Standard Intensive Treatment for Elderly Patients with AML and High Risk MDS - Janssen, Jeroen; Löwenberg, Bob; Manz, Markus; Bargetzi, Mario; Biemond, Bart; Borne, Peter von dem; Breems, Dimitri; Brouwer, Rolf; Chalandon, Yves; Deeren, Dries; Efthymiou, Anna; Gjertsen, Bjørn-Tore; et al. (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
Treatment results of AML in elderly patients are unsatisfactory. We hypothesized that addition of tosedostat, an aminopeptidase inhibitor, to intensive chemotherapy may improve outcome in this population. After establishing a safe dose in a run-in phase of the study in 22 patients, 231 eligible patients with AML above 65 years of age (median 70, range 66-81) were randomly assigned in this open label randomized Phase II study to receive standard chemotherapy (3+7) with or without tosedostat at the selected daily dose of 120 mg (n = 116), days 1-21. In the second cycle, patients received cytarabine 1000 mg/m2 twice daily on days 1-6 with or without tosedostat. CR/CRi rates in the 2 arms were not significantly different (69% (95% C.I. 60-77%) vs 64% (55-73%), respectively). At 24 months, event-free survival (EFS) was 20% for the standard arm versus 12% for the tosedostat arm (Cox-p = 0.01) and overall survival (OS) 33% vs 18% respectively (p = 0.006). Infectious complications accounted for an increased early death rate in the tosedostat arm. Atrial fibrillation was more common in the tosedostat arm as well. The results of the present study show that the addition of tosedostat to standard chemotherapy does negatively affect the therapeutic outcome of elderly AML patients.
Keywords: Aminopeptidase inhibitor; AML; Clinical trial; Elderly; High-risk MDS; Tosedostat; Oncology; Cancer Research; Journal Article